Rascet gorizontal'nych sil vzaimodejstvija sportsmena so štangoj pri pod"eme štangi na grud - Khasin, L. A.; Atkishkina, T. D.; Buryan, S. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
We consider weightlifting clean. The horizontal forces of interaction of the athlete with the barbell were calculated when performing the clean. To find the characteristics of the barbell movement were used high-speed (250 FPS) video recording of the clean. Presented: the algorithm we developed for calculating horizontal forces during contact of the barbell`s rod with the athlete`s hips; assessment of horizontal forces by shooting the end of the barbell parallel to the rod; graphs of horizontal forces arising during contact of the barbell`s rod with the athlete`s hips.